The perivascular niche of endometrial mesenchymal stromal/stem-like cells. Issue 4 (29th November 2022) - Chan, Rachel W. S.; Li, Tian-Qi; Zhang, Si-Si; Fang, Yuan; Xu, Jing-Wen
Abstract : Human endometrium is a unique adult tissue that undergoes cyclical shedding, repair, and regeneration during a woman's reproductive life. Over the past 2 decades, tremendous progress has been made towards the identification and characterization of endometrial stromal stem/progenitor cells . The substantial regeneration of vascularized stroma in the endometrium during the proliferative stages of each menstrual cycle is likely to be mediated by endometrial mesenchymal stromal/stem cells. This review focuses on the perivascular niche for CD140b + CD146 + pericytes and SUSD2 + perivascular cells. The identity, characteristics, and underlying mechanisms of uterine regeneration are also discussed.